European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30: factorial models to Brazilian cancer patients - Bonini Campos, Juliana Alvares Duarte [UNESP]; Bernardes Spexoto, Maria Claudia [UNESP]; Silva, Wanderson Roberto da [UNESP]; Serrano, Sergio Vicente; Maroco, Joao (Inst Israelita Ensino & Pesquisa Albert Einstein, 2018)
Objective: To evaluate the psychometric properties of the seven theoretical models proposed in the literature for European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), when applied to a sample of Brazilian cancer patients. Methods: Content and construct validity (factorial, convergent, discriminant) were estimated. Confirmatory factor analysis was performed. Convergent validity was analyzed using the average variance extracted. Discriminant validity was analyzed using correlational analysis. Internal consistency and composite reliability were used to assess the reliability of instrument. Results: A total of 1,020 cancer patients participated. The mean age was 53.3 +/- 13.0 years, and 62% were female. All models showed adequate factorial validity for the study sample. Convergent and discriminant validities and the reliability were compromised in all of the models for all of the single items referring to symptoms, as well as for the physical function and cognitive function factors. Conclusion: All theoretical models assessed in this study presented adequate factorial validity when applied to Brazilian cancer patients. The choice of the best model for use in research and/or clinical protocols should be centered on the purpose and underlying theory of each model.
Keywords: Quality of life; Neoplasms; Validation studies; Psychometrics